Acampavida: extensão universitária e intergeracionalidade - Souza, Juliana Gusman de (2018)
In 1998, the extension event Acampavida was structured, pioneering experience that aims to include the elderly of the city of Santa Maria and region in the university. The event is held once a year and didactic-cultural activities are developed in the form of mini-courses, workshops and lectures, coordinated and taught by professors and academics from UFSM and other HEIs. This research aimed to analyze the action of the extension event of Acampavida regarding the organization structure and the perception about intergenerationality of the elderly participants. Methodology of a qualitative nature, developed together with: (1) Elderly representatives of the groups of coexistence of the Third Age of Santa Maria that participate in the meetings that occur monthly in the Center of Physical Education and Sport, that is given in order to organize the Acampavida; (2) teachers coordinating the workshops; (3) Academic workshop monitors. The research techniques used were participant observation, semistructured interviews, documentary analysis and focus group, because it is understood that these techniques complement each other in relation to the proposed research object. Content analysis according to the method proposed by Bardin (2011). In the eighteen editions in which the event happened, the elderly actively participated in its construction, affirming its performance as social protagonists. For teachers and academics, the organization of the workshops made it possible to implement teaching, research and extension activities. In relation to the perceptions of the elderly about the interactions between the generations, it was verified that these are permeated by conflicts and solidarity, but that when they participate in the event, only the actions of solidarity are perceived. Thus, in observing the construction of the Acampavida, it was understood that in this space there are reciprocal exchanges from the wisdoms of each group, respecting the diversities and the knowledge of each one. Thus, it is believed that the more institutions that can foster coexistence in spaces such as the experience of Acampavida, the greater the opportunities to form new knowledge about aging.